The soils of Serbia and their degradation - Ličina, V., Faculty of Agriculture, Belgrade - Zemun (Serbia); Nešić, Lj., Faculty of Agriculture, Novi Sad (Serbia); Belić, M., Faculty of Agriculture, Novi Sad (Serbia); Hadžić, V., Faculty of Agriculture, Novi Sad (Serbia); Sekulić, P., Institute of Field and Vegetable Crops, Novi Sad (Serbia); Vasin, J., Institute of Field and Vegetable Crops, Novi Sad (Serbia); Ninkov, J., Institute of Field and Vegetable Crops, Novi Sad (Serbia) (Ratarstvo i povrtarstvo, 2011)
In view of the topicality of the subject of soil protection from degradation, the paper discusses some basic considerations concerning soil genesis, pedogenetic processes, and soil degradation caused by human activity in Serbia. It can be said that at present the main processes connected with soil loss and soil degradation in Serbia are as follows: 1) change in the intended use of the soil (soil loss and damage due to industrial, mining, and power-producing activities) 2) loss of soil organic matter, 3) acidification and salinization of soil, 4) different forms of soil contaminations (as a result of the excessive use of agrochemicals, heavy metals, industrial pollution, etc.), 5) aeolian and water erosion, and 6) compaction and other types of physical degradation of agricultural soil. The most important aspects of soil protection from degradation are preventive measures, the identification of potential dangers, and the finding of ways to overcome them. Only usage of systematic monitoring of soil quality and other tools provide proper results in the protection of the soil from degradation.